Meningkatkan Kepatuhan Pajak di Kalangan UMKM: Studi Pada Pemilik Usaha Mikro Kecil dan Menengah di Kabupaten Polewali Mandar - Arifin, Arifin (Politeknik Ganesha Medan, 2024)
This research aims to examine and analyze the influence of tax determinants on the compliance of individual SME taxpayers in Polewali Mandar. By collecting and analyzing data from respondents in Polewali Mandar, this study explores the relationship between tax knowledge, tax rates, and tax penalties with SME taxpayer compliance. The findings provide valuable insights into understanding the factors affecting taxpayer compliance at the SME level. The results indicate that tax knowledge has a positive but insignificant effect on the compliance of individual SME taxpayers in Polewali Mandar. This emphasizes the importance of enhancing understanding of the tax system from calculating to reporting taxes, as an effort to improve taxpayer compliance. Moreover, the study finds that tax rates have a positive and significant influence on the compliance of individual SME taxpayers in Polewali Mandar. The implementation of regulations regarding Final Income Tax at a rate of 0.5% for SMEs is perceived as a measure that eases tax payments, thereby enhancing taxpayer compliance. Furthermore, tax penalties are proven to have a positive and significant effect on the compliance of individual SME taxpayers in Polewali Mandar. The existence of tax penalties is regarded as a strong incentive to foster discipline in fulfilling tax obligations. By enforcing tax penalties for all violators, it is expected to promote increased taxpayer compliance from payment to tax reporting. This research provides an in-depth understanding of the importance of tax determinant factors in influencing SME taxpayer compliance. Therefore, efforts to enhance tax knowledge, ensure fair tax rates, and enforce strict tax penalties can be effective strategies in improving taxpayer compliance at the individual SME level in Polewali Mandar.